Comparative description of the mitochondrial genome of Scaphidium formosanum Pic, 1915 (Coleoptera: Staphylinidae: Scaphidiinae) - Zhao, Tian-You; Zhang, Cheng-Jia; Lü, Liang (Zootaxa, 2021)
Scaphidium is a rove beetle genus (Coleoptera: Staphylinidae) of remarkable and diverse colouration. Although most of Scaphidium species are easily distinguished by the colour patterns, there exist some confusing variants, which may introduce bias into rapid identification. Molecular identification using the mitochondrial genome is a reliable approach that overcomes the shortcoming of morphological recognition for those who have limited experience in species-level identification. Here we described the nearly complete mitochondrial genome of Scaphidium formosanum Pic, 1915, a species with variant colour types, and tested the reliability of identification based on mitochondrial genes by both gene-wise metrics and phylogenetic analyses. In this study, the 17,455 bp mitochondrial genome of S. formosanum is composed of 13 protein-coding genes (PCGs), 22 tRNAs, and 2 rRNAs. All PCGs start with typical ATN codons, except Nad4l which began with the TTG codon. The gene order is consistent with the typical linear arrangement of the published rove beetle mitochondrial genomes. The nucleotide composition is highly A+T biased (76.42%): A - 39.99%, T - 36.44%, C - 15.08%, and G - 8.49%. Multiple metrics support that our sample has a higher similarity to S. quadrimaculatum than to other species. Maximum likelihood trees confirm the placement of our sample as the closest related entity to S. quadrimaculatum. We conclude that the mitochondrial genome has a reliable performance in molecular identification in this case.